2019
DOI: 10.1124/jpet.118.252940
|View full text |Cite
|
Sign up to set email alerts
|

The HNF1α-Regulated LncRNA HNF1α-AS1 Is Involved in the Regulation of Cytochrome P450 Expression in Human Liver Tissues and Huh7 Cells

Abstract: Expression of cytochrome P450s (P450s) is regulated by epigenetic factors, such as DNA methylation, histone modifications, and noncoding RNAs through different mechanisms. Among these factors, long noncoding RNAs (lncRNAs) have been shown to play important roles in the regulation of gene expression; however, little is known about the effects of lncRNAs on the regulation of P450 expression. The aim of this study was to explore the role of lncRNAs in the regulation of P450 expression by using human liver tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…LncRNAs are other non-coding transcripts with longer than 200 nucleotides length, and have a pivotal role in promoting of wide spectrum disorders from cancer to neurodegenerative diseases. Recently, studies on human liver tissues and Huh7 cells demonstrated the positive correlation between expression levels of lncRNA hepatocyte nuclear factor 1 alpha antisense 1 ( HNF1a-AS1 ), and several CYP enzymes including CYP2C8, 2C9, 2C19, 2D6, 2E1, and 3A4 ( Wang et al, 2019 ). The liver-specific triglyceride regulator ( lnc-Ls tr) modulates the triglyceride plasma levels in mice by counteracting the repressor effects of TAR DNA binding protein 43 (TDP-43) on CYP8b1 promoter.…”
Section: Expression Levels Of Cyp450 Variants Are mentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are other non-coding transcripts with longer than 200 nucleotides length, and have a pivotal role in promoting of wide spectrum disorders from cancer to neurodegenerative diseases. Recently, studies on human liver tissues and Huh7 cells demonstrated the positive correlation between expression levels of lncRNA hepatocyte nuclear factor 1 alpha antisense 1 ( HNF1a-AS1 ), and several CYP enzymes including CYP2C8, 2C9, 2C19, 2D6, 2E1, and 3A4 ( Wang et al, 2019 ). The liver-specific triglyceride regulator ( lnc-Ls tr) modulates the triglyceride plasma levels in mice by counteracting the repressor effects of TAR DNA binding protein 43 (TDP-43) on CYP8b1 promoter.…”
Section: Expression Levels Of Cyp450 Variants Are mentioning
confidence: 99%
“…Furthermore, growing body of evidence demonstrated that several factors including CYP450 single nucleotide polymorphisms (SNPs), and epigenetic molecules such as non-coding RNAs (ncRNAs), DNA methylation and histone acetylation influenced the expression levels of CYP450 , and consequently might influence HCQ metabolism. ( Li et al, 2015 ; Zeng et al, 2017 ; Wang et al, 2019 ). The major purpose of this review is to discuss the pharmacokinetic and pharmacodynamic characteristics of CQ and HCQ that may be influenced by epigenetic mechanisms including ncRNAs and CYP2D6 SNPs, and thereby cause several side effects such as cardiotoxicity, prolonged QT interval, gastrointestinal problems (like dyspepsia and abdominal cramps), central nervous system or skin disorders, and especially retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a positive correlation was observed in human liver tissue samples between increased mRNA levels for HNF1A, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP3A4, PXR, and CAR and upregulation of HNF1A-AS1 lncRNA. 156 Although correlations in expression are consistent with this regulatory network, the underlying mechanisms remain elusive.…”
Section: Lncrna-mediated Cyp Expressionmentioning
confidence: 96%
“…miR-214–3p targets CYP2E1 at the coding sequence, while miR-552, miR-570, and miR-378a-5p target its 3′-UTR [ 39 ]. The lncRNAs hepatocyte nuclear factors 1A antisense-RNA-1 (HNF1A-AS1) and 4A antisense-RNA-1 (HNF4A-AS1) are important regulators of CYP gene expression as well, interfering with the xenobiotic-dependent CYP2E1 bioactivation [ 40 ].…”
Section: Roles Of Ncrnas In Environmental Healthmentioning
confidence: 99%